التعايش السلمي بين الأديان في ضوء الكتاب والسنة: Peaceful Co-existence among Religions in the light of Quran and Sunnah - Dr. Abdul Wahab Jan, (MEI, 2023)
Al-Zarkashi is one of the scholars who deny the occurrence of synonymy between the words of the language, as he sees that the words were distributed according to the denominators, so their synonyms cannot be used in what is used in the place of the other. The meaning is not the meaning of the individuals, and for this reason many fundamentalists from his point of view prevented one of the synonyms from taking the place of the other in the composition, and if they agreed on its permissibility in the singular and the contemplative in the previous words of Al-Zarkashi, he finds that although he is one of those who say that the synonymy between words does not occur, his opinion differs from The opinion of the two previous groups, so if those who say that the synonym occurs in Arabic have exaggerated in it and captured it a lot.